Effect of CNTs dispersion on the thermal and mechanical properties of Cu/CNTs nanocomposites - ., Ali Samer Muhsan, Faiz Ahmad, Norani M Mohamed, Puteri Sri Melor (2014)
Modified technique of metal injection molding (MIM) was used to fabricate multiwalled carbon nanotube (CNT) reinforced Cu nanocomposites. The effect of adding different amount of CNTs (0-10 vol.%) on the thermal and mechanical behaviour of the fabricated nanocomposites is presented. Scanning electron microscope analysis revealed homogenous dispersion of CNTs in Cu matrices at different CNTs contents. The experimentally measured thermal conductivities of Cu/CNTs nanocomposites showed extraordinary increase (76% higher than pure sintered Cu) with addition of 10 vol.% CNTs. As compared to the pure sintered Cu, increase in modulus of elasticity (Young's modulus) of Cu/CNTs nanocomposites sintered at 1050°C for 2.5 h was measured to be 48%. However, in case of 7.5 vol.% CNTs, Young's modulus was increased significantly about 51% compared to that of pure sintered Cu.